Advance in Friction Stir Processed Materials - Iwaszko, Józef; Winczek, Jerzy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint presents the current state of knowledge and the latest advances in the development of microstructure and material properties using modern FSP (Friction Stir Processing) and related technologies such as FSW (Friction Stir Welding). The chapters of this reprint contain valuable results of research on changes in the microstructure and properties of materials caused by the use of the above technologies. Detailed analysis of these results allowed for the formulation of constructive conclusions of scientific and technological importance. The issues described in here present a significant cognitive and application potential and indicate the problems and implementation challenges faced by users of FSP and related technologies.